Medieval mad science: Depicting scientists in HBO's Game of Thrones. Issue 1 (1st March 2019) - Gil, Steven
With its medieval-styled sword and sorcery, Game of Thrones hardly presents a narrative world where we would expect to find science or scientists. Yet science plays a prominent role in the high-fantasy narrative and at the centre of this is Qyburn, a scientist figure worth detailed consideration. Using the perennial sociocultural concept of the mad scientist as the starting point, this article examines how the morally complex world of Game of Thrones presents science as dangerous yet essential to the boundary breaking necessary for the creation of new medical and technical knowledge.